1993
DOI: 10.1111/j.1365-2826.1993.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Function in Rat Pituitary Intermediate Lobe is Inhibited by an Endogenous Protein

Abstract: Though glucocorticoids inhibit proopiomelanocortin (POMC) gene expression and POMC-derived peptide release from corticotroph cells of the anterior pituitary, the regulation of this gene by glucocorticoids is less clear in the melanotroph cell of the pituitary intermediate lobe. To examine the difference between glucocorticoid sensitivity of the anterior lobe (AL) and intermediate lobe (IL) of the pituitary we have examined glucocorticoid receptor (GR) status of these two tissues and the role glucocorticoids pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Exposure time: 15 days. pars intermedia has been reported (Bertini et al 1989 (Sheppard et al 1993). In the pars intermedia of the fetal sheep, POMC mRNA is translated and processed to immunoreactive ACTH (Matthews et al 1994).…”
Section: Pars Intermediamentioning
confidence: 93%
See 1 more Smart Citation
“…Exposure time: 15 days. pars intermedia has been reported (Bertini et al 1989 (Sheppard et al 1993). In the pars intermedia of the fetal sheep, POMC mRNA is translated and processed to immunoreactive ACTH (Matthews et al 1994).…”
Section: Pars Intermediamentioning
confidence: 93%
“…Analysis of the developing rat pituitary revealed high levels of GR mRNA in the pars distalis, specifically in cells exhibiting ACTH immuno¬ reactivity (Cintra et al 1993). GR immunoreactivity is also present in the rat pars intermedia (Bertini et al 1989), and glucocorticoids have been shown to regulate pro¬ opiomelanocortin (POMC) heteronuclear RNA and mRNA in this region (Seger et al 1988, Sheppard et al 1993, indicating the presence and function of GRs in this region of the gland.…”
Section: Introductionmentioning
confidence: 96%
“…The regulation of POMC transcription, however, is tissue specific. The inability of glucocorticoids to affect POMC in the intermediate lobe of the pituitary can be attributed to the absence of functional glucocorticoid receptors on these intermediate lobe cells, although glucocorticoid receptor mRNA has been detected in these cells [22, 23]. Functional glucocorticoid receptors can be induced in these cells if the neural input to the intermediate is disrupted [22, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were then incubated in the absence (a-c) or presence (d-f) of 1 nM OT for 2 h. The bars correspond to the meanf SEM of 3 experimental wells within the same experiment. Significant statistical differences (Pc0.05) were observed between the following groups: (a) vs (b), (b) vs (c) and (c) vx (d).detected low levels of immunoreactive GR on rat melanotrophs, Sheppard et a/ (35). demonstrated that these receptors lacked functional activity, since their ability to regulate POMC gene expression was blocked by the presence of inhibitory proteins.…”
mentioning
confidence: 88%